Telehealth as a Psychological Intervention for Caregivers of Children with Neurodevelopmental Disorders: A Systematic Review with Effect Sizes. - Kelson, Ellen; Dorstyn, Diana (Journal of Autism & Developmental Disorders, 2025)
Caregivers of children with a neurodevelopmental disorder report increased mental health difficulties but also barriers to accessing professional support. Psychological interventions via telehealth offer an accessible method of service delivery for these families. This review is the first to quantitatively evaluate available telehealth trials designed to promote caregivers' mental health. The PubMed, PsycINFO, CINAHL, Embase and Cochrane databases (from inception until 20th May 2023) were searched for telehealth trials targeting caregiver mental health. Hedges' g effect sizes were calculated, and findings reported by symptom domain (depression, anxiety, stress, distress), telehealth format (individual vs. group), and modality (webpage, text-messaging, video). Reporting bias (QualSyst tool) and publication bias (Doi plot) were also assessed. Twelve independent studies (N = 769 caregivers), including eight controlled trials and four quasi-experimental (pre-post, single group) designs, were included. Most studies were of acceptable methodological quality. Evidence for improved mental health was found for telehealth (g range = 0.394–1.955), regardless of the method of delivery. The longevity of these effects could not, however, be determined. The present findings suggest that psychological interventions delivered by telephone and/or the internet can be used to effectively manage caregivers' mental health symptoms, although consideration must be given to an individual's treatment preferences and requirements. Further non-inferiority trials, with a diverse sample, can determine whether telehealth interventions provide a comparable alternative to face-to-face treatment. Protocol registration on Open Science Framework: https://osf.io/ctqne/.